Importance of Creative Advertising and Marketing According to University Students' Perspective - Terkan, Remziye (International Review of Management and Marketing, 2014)
Advertising has crucial role in todays competitive marketing world. This research studies two important persuasive processes often employed in the management of businesses; Creative Advertising and Marketing Management. Creative Advertising and Marketing Management is necessary in order to have a complete understanding of how producers and sales companies work effectively. While advertising performs the communicative function of informing consumers about a company’s product or services, creative advertising is also attract people to the market, marketing management is a much more complex managerial process which encompasses activities such as; marketing research, product conception and design, pricing, distribution and even advertising. Today, in current globalized and rapidly expanding business conscious world; creative advertising and marketing management are increasingly becoming more relevant to the businesses. Companies need to adopt creative strategies and innovations in their operations in order to survive the challenges of the ever expanding global market. In the study, creative advertising and its importance in marketing managemet are investigated and examined by sample group of university students. Keywords: Creative advertising; Innovations; Marketing management; Persuasion in marketing JEL Classifications: M31